The Influence Of Compensation And Training Towards Emloyee Performance With Job Satisfaction As An Interverning Variable In PT EN. - Ghea Aprilly K Pramesti; Singmin Johanes Lo (Dinasti Publisher, 2024)
This study aims to analyze the influence of compensation and training on employee performance with job satisfaction as Intervening Variable at PT EN with population and sample 67 employees with at least one year work experience at PT EN. The data collecting method is questionnaire, analyzed using model of structural equation modeling (SEM). The result of the research show that compensation have posssitive and significant effect on Job satisfaction, training have positive and significant effect on Job satisfaction, Job satisfaction have positive and significant effect on employee performance, Compensation have positive and signivcant effect on employee performance through job satisfaction, Training have positive and significant effect on employee performance through job satisfaction.